2001
DOI: 10.1021/ac010939i
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Electrophoretic Mobility Distributions through the Analysis of Individual Mitochondrial Events by Capillary Electrophoresis with Laser-Induced Fluorescence Detection

Abstract: Here we report on the analysis of mitochondrial preparations by capillary electrophoresis with postcolumn laser-induced fluorescence detection. Individual mitochondria are detected by fluorescent labeling with the mitochondrion-selective probe, 10-nonyl acridine orange. Interactions between the organelles and the capillary walls are controlled by derivatization of the capillaries with poly(acryloylaminopropanol). As expected from the presence of charged groups in their outer membranes, isolated mitochondria ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 32 publications
3
120
1
Order By: Relevance
“…Previous reports on the CE-LIF analysis of mitochondrial samples, showed that for samples containing ∼50 events, the electrophoretic mobility histograms are flat and broadly distributed [8], while for samples containing ∼2000, the corresponding histograms appear more Gaussian in nature [21]. This suggests that sample size is important when analyzing individual particles and statistical descriptions are needed to help identify how the number of events affects a distribution.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports on the CE-LIF analysis of mitochondrial samples, showed that for samples containing ∼50 events, the electrophoretic mobility histograms are flat and broadly distributed [8], while for samples containing ∼2000, the corresponding histograms appear more Gaussian in nature [21]. This suggests that sample size is important when analyzing individual particles and statistical descriptions are needed to help identify how the number of events affects a distribution.…”
Section: Introductionmentioning
confidence: 98%
“…The capability of CE systems, equipped with laser-induced fluorescence (LIF) detectors, to separate individual organelles has also been demonstrated [8]. Although flow cytometry was historically used first to detect individual organelles [9,10], CE has the additional analytical advantage of being able to separate organelles based on their electrophoretic mobilities [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2), which is due to the size heterogeneity of mitochondrial particles and the presence of some mitochondrial fragments and aggregates in the sample [32]. Fortunately, particles that are similar in size to mitochondria have been shown to have electrophoretic mobilities independent of size [33].…”
Section: Identifying Sampling Effects On Mitochondrial Distributionsmentioning
confidence: 96%
“…The design and setup of the electrophoresis system with sheath flow cuvette postcolumn LIF detection used in this study have been previously described [32,33]. A single-line argon-ion laser (488 nm, 12 mW) was used for fluorescence excitation (Melles Griot, Irvine, CA).…”
Section: Cementioning
confidence: 99%